The study of the indigenous and local fruits of Hulu Samarahan area - Cartina Luyau, ak Sulau. (Universiti Malaysia Sarawak (UNIMAS), 2004)
A study on indigenous and common local fruits was carried out at Hulu Samarahan area involving thxee (3) villages to document its uses and preparations among the Iban community. Forty six (46) species of indigenous and common local fruits from twenty five (25) families were recorded. The specimens collected were preserved and kept at University Malaysia Sarawak Herbarium (HUMS). Most of the fruits were commonly found in the small orchard and garden. The famous indigenous fruits in Sarawak are Dabai (Canarium odonlophyllum Hook.f), Kembayau (Dacryodes roslala j cuspidala), Engkala (Lilsea garciae Merr. and Derr.), Ucung (Baccaurea angulala Merr.), Engkilili (Lepisanlhes alala (BI.) Leenh) and Keranji (Dialium cochinchinense Pierre). Indigenous fruit like Dabai ( Canarium odonlophyllum) is one of the most potential and highly commercialize in the local market. Most of the indigenous fruits are already domesticated grown in garden and wild in the forest. Fruits like Dabai (Canarium odonlophyllum), Kembayau (Dacryodes roslalaj cuspidala), Durian nyekak (Durio kUlejensis Merr.) and Durian kuning (Durio graveolons Becc.) are very nutritious with high values or energy, protein and potassium. Meanwhile, common local fruits such as pineapple (Ananas comosus (L.) Merr.), Mangostene (Garcinia mangoslana L.) and papaya (Carica papaya L.) are highly remarkable sources of wholesome food and valuable for flavour and aroma. Study are still needed to record all indigenous frits and hopefully our local fruits will be getting popular and as an important source of income for the local communities in Sarawak.